Clinical and epidemiological features of coryneform skin infections at a tertiary hospital - Malcolm Pinto; Ganesh Kamath Hundi; Ramesh Marne Bhat; Nanda Kishore Bala; Sukumar Dandekeri; Jacintha Martis; Srinath M Kambil (Wolters Kluwer Medknow Publications, 2016)
Background: Skin infections caused by coryneform bacteria are common dermatological conditions. However, to the best of our knowledge, no studies are available on the clinical characteristics and epidemiological features of this group of disorders as one entity from India and abroad. Aims: To study the clinical and epidemiological features of coryneform skin infections Methods: A total of 75 patients presenting with clinically distinctive lesions of pitted keratolysis, erythrasma and trichobacteriosis to our hospital were included in the study. Cases were interviewed with particular emphasis on epidemiological features and the various clinical findings were recorded. Investigations like Gram's stain, Wood's light examination, 10% KOH scrapings, were done in selected cases to ascertain the diagnosis. Results: Pitted keratolysis was more common in the age group of 31-40 years (40%) with a male preponderance (76.7%), most commonly affecting pressure bearing areas of the soles with malodour (86.7%) and frequent contact with water (58.3%) constituting the most important presenting symptom and provocating factor respectively. Erythrasma affected both male and female patients equally and was more commonly detected in patients with a BMI > 23kg/m2 (62.5%) and in diabetics (50%). All patients with trichobacteriosis presented with yellow coloured concretions in the axillae. Bromhidrosis (71.4%) and failure to regularly use an axillary deodorant (71.4%) were the most common presenting symptom and predisposing factor respectively. Conclusion: Coryneform skin infections are common dermatological conditions, though epidemiological data are fragmentary. Hyperhidrosis is a common predisposing factor to all three coryneform skin infections. Asymmetrical distribution of pits has been reported in our study. Diabetic status needs to be evaluated in all patients with erythrasma. Woods lamp examination forms an indispensible tool to diagnose erythrasma and trichobacteriosis.